Forming facilities of project competence for future grid automation engineers - Rudevich, N. (Problems of Engineer-Pedagogical Education, 2018)
The article is sanctified to development of teaching facilities for forming of project competence for future grid automation engineers on the basis of cause and effect model of knowledge and corresponding teaching methodologies. The teaching facilities are worked out for the study of realization of tasks of including on parallel work, liquidation of the asynchronous mode and protecting from the coil shorting of synchronous generator. The teaching facilities are created taking into account the features of construction of basic types of control system by the objects of grids, namely automatics of the normal modes, anti-fault automation and relay protection. The teaching facilities are worked out according to the basic stages of teaching method for forming of project competence for future gridautomation engineers: acquaintance with the object of management; forming of knowledge, abilities, skills on determination of requirements, setting, principle of action and structure of making elements of control system; forming of knowledge, abilities, skills on determination of realization and parametersof making elements of control system.